Senam Hipertensi Dalam Upaya Meningkatkan Kesehatan Lingkungan di Desa Karya Indah Kecamatan Tapung Kabupaten Kampar - ezalina ezalina (Universitas Muhammadiyah Mataram, 2026)
Hypertension is one of the most common non-communicable diseases (NCDs) and a leading cause of death due to cardiovascular disorders. In Indonesia, the prevalence of hypertension remains high, reaching 34.1% among adults aged ≥18 years (Riskesdas, 2018). This condition highlights the need for promotive and preventive efforts through non-pharmacological approaches, one of which is hypertension exercise. This community service activity aimed to improve public knowledge, skills, and motivation in preventing and controlling hypertension through health education and hypertension exercise practice. The activity was carried out on September 28, 2025, at Pasum RT 40 Stage 3, Karya Indah Village, Tapung District, Kampar Regency, involving 30 participants consisting of housewives, the elderly, health cadres, and the general public. The implementation consisted of three stages: preparation, execution, and evaluation. The results showed an increase in participants’ understanding of hypertension, its risk factors, and the health benefits of hypertension exercise. Participants were able to perform the movements correctly and expressed commitment to practicing them regularly. The activity also fostered enthusiasm and collective awareness toward healthy living. This program demonstrates that health education combined with practical exercise is an effective strategy to enhance community awareness and encourage healthy lifestyles to prevent hypertension complications.